37.2: Efficiency Improvement of Fluorescent Blue Device by Molecular Orientation of Blue Dopant. Issue 1 (1st July 2013) - Ogiwara, Toshinari; Ito, Hirokatsu; Mizuki, Yumiko; Naraoka, Ryo; Funahashi, Masakazu; Kuma, Hitoshi
Abstract: The relationship between molecular shape of fluorescent blue dopants (BDs) and molecular orientation factor was studied. BDs with larger ovality showed higher orientation factor and higher EQE over 10% in a fluorescent blue device. Impedance spectroscopy, transient EL spectroscopy and optical simulation results highly indicate that such high EQE is originated mainly from the optical effect of horizontal‐aligned BDs. Furthermore, a higher EQE of 11.5% at a current density of 10mA/cm 2 was successfully achieved by modifying molecular structure of BD.